2011
DOI: 10.3109/15412555.2011.594463
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Three Instruments to Assess Self-Reported Functional Status in Patients with COPD

Abstract: The study aimed to compare the responsiveness of three instruments to assess self-reported changes in functional status after exercise training in patients with COPD: Pulmonary Functional Status and Dyspnea Questionnaire -modified version (PFSDQ-M), London Chest Activity of Daily Living (LCADL) and Medical Research Council scale (MRC). Twenty-two patients (11 female, 66[62-71] years, FEV1 42[33-61]%predicted) participated in a 3-month high-intensity exercise program. The three instruments were applied pre- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
1
2
1
1
Order By: Relevance
“…However, daily dyspnea (as assessed by the LCADL scale) apparently did not affect the performance of ADL; no correlations were found between LCADL scale scores and the results obtained with the accelerometer. Nevertheless, although the LCADL is apparently better for self-assessed changes in COPD patients undergoing training programs than is the mMRC scale, ( 27 ) the difference between the COPD patients and the controls in the present study was four times greater than the change obtained by such programs.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, daily dyspnea (as assessed by the LCADL scale) apparently did not affect the performance of ADL; no correlations were found between LCADL scale scores and the results obtained with the accelerometer. Nevertheless, although the LCADL is apparently better for self-assessed changes in COPD patients undergoing training programs than is the mMRC scale, ( 27 ) the difference between the COPD patients and the controls in the present study was four times greater than the change obtained by such programs.…”
Section: Discussioncontrasting
confidence: 73%
“…Entretanto, a dispneia diária durante a realização de AVD registradas pelo LCADL não pareceu interferir, já que não foram encontradas correlações entre o LCADL e os dados obtidos com o acelerômetro. Por outro lado, os valores de LCADL encontrados no presente estudo reforçam que esse é um instrumento melhor que a escala mMRC, tanto para a avaliação de pacientes submetidos a programas de treinamento, ( 27 ) quanto na situação basal: os pacientes avaliados apresentavam resultados quatro vezes piores que os controles.…”
Section: Discussionunclassified
“…Rehabilitation resulted in statistically significant improvements in the 6MWT walking distance ( p < 0.001), with a small effect size (Cohen’s d = 0.45). These findings are in accordance with multiple studies, confirming that pulmonary rehabilitation of varying duration, frequency, intensity, and type, leads to improvements in walking distance in patients with COPD [ 8 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…These include the Canadian Occupational Performance Measure (COPM), London Chest ADL (LCADL) Scale, Manchester Respiratory ADL Scale and the Pulmonary Functional Status and Dyspnoea Questionnaire 27–30. Prospective uncontrolled studies suggest that pulmonary rehabilitation does impact on ADL 25 31 32. Sewell et al 25 compared an individualised exercise programme with a generic exercise programme and demonstrated statistically significant within-group improvements in COPM performance and satisfaction scores for both treatment groups.…”
Section: Evidencementioning
confidence: 99%
“…A further uncontrolled study has shown improvements in LCADL Scale scores 31. A small study of 22 patients compared three measures of self-reported ADL and concluded that the LCADL and modified version of the pulmonary functional status and dyspnoea questionnaire (PFSDQ-M) were more responsive than the MRC scale 32. However, the impact of pulmonary rehabilitation upon ADL has not been reported in a RCT comparing pulmonary rehabilitation with usual care.…”
Section: Evidencementioning
confidence: 99%